Mesenchymal Stem Cells Application in Wound Tissue Healing in Old Animals - Silina E (Dove Medical Press, 2020)
Ekaterina Silina,1 Natalia Manturova,2 Victor Stupin3 1Department of Human Pathology, I.M. Sechenov First Moscow State Medical University (Sechenov University), Moscow, Russia; 2Department of Plastic and Reconstructive Surgery, Cosmetology and Cell Technologies, Pirogov Russian National Research Medical University, Moscow, Russia; 3Department of Hospital Surgery №1, Pirogov Russian National Research Medical University, Moscow, RussiaCorrespondence: Ekaterina SilinaDepartment of Human Pathology, I.M. Sechenov First Moscow State Medical University (Sechenov University), Trubetskaya Street, 8, Moscow 119991, RussiaEmail silinaekaterina@mail.ruPurpose: An assessment of the effectiveness of progenitor mesenchymal stem cell as injections and as part of a polymer hydrogel for the wounds treatment.Materials and Methods: Fixed-size wounds (average area of 135.8 mm2) were modeled on the back of white Wistar rats, aged 9 months. Mesenchymal stem cells (MSC) isolated from a human umbilical cord were injected into the wounds once on the modeling day (SC group). In other animals, MSC were periodically applied externally as one of the components in the polymer hydrogel (Polymer_sc group). The systemic effect of the cells was assessed via the analysis of intact contralateral wounds located on the opposite side of the same animal’s back (groups Control_sc and Control_Psc, respectively). The reference intact wounds belonged to the Control_0 group. The wound area was studied in dynamics. Descriptive microscopy was supplemented by an assessment of the collagen fibers’ maturity, the epidermal layers, and the number of fibroblasts and leukocytes in different parts of the wounds.Results: Both the local and systemic application of MSC led to an improvement in wound regeneration. During the acute inflammatory phase (up to 3 days), the method and place of application did not affect the dynamics of wound healing. The use of Polymer_sc ultimately demonstrated the best effectiveness. The anti-inflammatory effect of MSC was confirmed by a decrease in leukocyte infiltration in the wound centers (Polymer_sc and SC groups) and edges (all groups, with the greatest extent in the Polymer_sc group). The proliferative phase that expresses itself via accelerated growth in fibroblast number and collagen production was affected in the Control_Psc group and mostly in the Polymer_sc group.Conclusion: The applications of MSC in various ways improve and accelerate wound healing even in old animals. The best performance was achieved in the Polymer_sc group.Keywords: stem cells, umbilical cord cells, adult animals, fibroblasts, leukocytes, wound, wound treatment, regeneration, wound area, collagen, skin, epidermis, epithelium, polymers, injections, local and systemic action of stem cells